Survey of Preventable Disaster Death at Medical Institutions in Areas Affected by the Great East Japan Earthquake: A Retrospective Preliminary Investigation of Medical Institutions in Miyagi Prefecture. Issue 2 (27th February 2015) - Yamanouchi, Satoshi; Sasaki, Hiroyuki; Tsuruwa, Miho; Ueki, Yuzuru; Kohayagawa, Yoshitaka; Kondo, Hisayoshi; Otomo, Yasuhiro; Koido, Yuichi; Kushimoto, Shigeki
Abstract: Problem: The 2011, magnitude (M) 9, Great East Japan Earthquake and massive tsunami caused widespread devastation and left approximately 18, 500 people dead or missing. The incidence of preventable disaster death (PDD) during the Great East Japan Earthquake remains to be clarified; the present study investigated PDD at medical institutions in areas affected by the Great East Japan Earthquake in order to improve disaster medical systems. Methods: A total of 25 hospitals in Miyagi Prefecture (Japan) that were disaster base hospitals (DBHs), or had at least 20 patient deaths between March 11, 2011 and April 1, 2011, were selected to participate based on the results of a previous study. A database was created using the medical records of all patient deaths (n=868), and PDD was determined from discussion with 10 disaster health care professionals. Results: A total of 102 cases of PDD were identified at the participating hospitals. The rate of PDD was higher at coastal hospitals compared to inland hospitals (62/327, 19.0% vs 40/541, 7.4%; P <.01). No difference was observed in overall PDD rates between DBHs and general hospitals (GHs); however, when analysis was limited to cases with an in-hospital cause of PDD, the PDD rate was higher at GHs compared to DBHs (24/316, 7.6% vs 21/552, 3.8%; P <.05). The most common causes of PDD were: insufficient medical resources, delayed medical intervention, disrupted lifelines, deteriorated environmental conditions in homes and emergency shelters at coastal hospitals, and delayed medical intervention at inland hospitals. Meanwhile, investigation of PDD causes based on type of medical institution demonstrated that, while delayed medical intervention and deteriorated environmental conditions in homes and emergency shelters were the most common causes at DBHs, insufficient medical resources and disrupted lifelines were prevalent causes at GHs. Conclusion: Preventable disaster death at medical institutions in areas affected by the Great East Japan Earthquake occurred mainly at coastal hospitals. Insufficient resources (at GHs), environmental factors (at coastal hospitals), and delayed medical intervention (at all hospitals) constituted the major potential contributing factors. Further investigation of all medical institutions in Miyagi Prefecture, including those with fewer than 20 patient deaths, is required in order to obtain a complete picture of the details of PDD at medical institutions in the disaster area. S Yamanouchi, H Sasaki, M Tsuruwa, Y Ueki, Y Kohayagawa, H Kondo, Y Otomo, Y Koido, S Kushimoto .Survey of preventable disaster death at medical institutions in areas affected by the Great East Japan Earthquake: a retrospective preliminary investigation of medical institutions in Miyagi Prefecture .Prehosp Disaster Med .2015 ;30 (2 ):1 -7 .